Meningkatkan dimensi Gotong Royong Siswa dalam Pembelajaran PAK Metode PBL Fase F SMKN 1 Mook Manaar Bulatn - Martinus Kopong Laga; Andarweni Astuti; Hartutik Hartutik; Sugiyana Sugiyana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research is a process carried out in improving the faith and morals and the spirit of mutual cooperation of students through the application of the problem based learning (PBL) learning model on the material: Building a Culture of Love for class XI of SMKN 1 Mook Manaar Bulatn, West Kutai-East Kalimantan. The method used in this research is from Classroom Action Research (CAR) which is carried out in 2 (two) cycles. And in the cycle, it is passed through the planning, implementation, class observation, and joint reflection stages. The CAR places class XI students; both in the expertise competencies of Plantation Crop Agribusiness (ATP) and Office Management and Business Services (MPLB) totaling 8 (eight) people. as research subjects. The data obtained is a summary of the test, observation and interview processes. The results of the CAR research confirm that the application or implementation of the PBL model as one of the learning models can improve faith and morals and the spirit of mutual cooperation for students. This is indicated by the increase in the average value of students in each cycle and the active participation of students in the ongoing learning process. Based on this process, it can be seen that the application of the PBL model in the material: Building a Culture of Love is effective in improving the quality of learning, especially in the aspects of faith and morals and mutual cooperation. Thus, it is recommended that educators apply problem-based learning models more often in the learning process in order to improve the understanding and skills of students who are increasingly qualified.